Green Synthesis of Nanocomposite: Based on [Eugenol and Metal Oxides], Characterization and Biomedical Applications (Baghdad Science Journal, 2024)
Eugenol (EUG) was reacted as a matrix with a mixture of metal oxides (ZnO and CuO) have been prepared from metal acetate, Zn (CH3CO2)2 and Cu (CH3CO2)2 as precursors and using ethylene glycol (EG) as a solvent for synthesis the [Eug/ ZnO: CuO] nanocomposite using Sol-Gel method. The synthesized nanocomposite was characterized using techniques (FT-IR, AFM, SEM, EDX, and XRD), where the average particle diameter was found to be within the nanoscale range. It was also observed that the prepared nanomaterial was in the form of rods with good homogeneity distribution. In order to stand on the obtained nanoscale properties, those properties were employed in terms of nanoscale dimension and shape characteristics, to investigate the effectiveness of the prepared nanocomposite [Eug/ ZnO: CuO] as antimicrobials (antibacterial and antifungal) activity against two types of bacteria [Escherichia Coli (-) (E. coli), and Staphylococcus aureus (+) (S. aureus)], and one type of fungi [Candida albicaus (C. albicaus)], where it showed acceptable results. The effectiveness of the prepared nanocomposite was also measured as the antioxidant against free radicals and it showed a good scavenging ratio. In addition, the cytotoxic effect of [Eug/ ZnO: CuO] nanocomposite on breast cancer cells (MCF-7) was studied, and it showed acceptable results in killing the cell line (MCF-7) at high concentrations.